2005
DOI: 10.1515/jpem.2005.18.4.363
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the Growth Hormone/Insulin-like Growth Factor-I Axis in Critically Ill Children

Abstract: Critical illness has an important impact on the human endocrine system. Very few studies have been performed to elucidate the alterations of the GH/IGF-I axis in acutely ill children. The aim of this study was to investigate several parameters of this axis in children with trauma (TRA) and sepsis (SEP) requiring admission to the pediatric intensive care unit (PICU). A total of 16 children, ten with TRA and six with SEP (age 1-10 years) as well as 18 healthy children (CS) of similar age and gender were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 31 publications
(18 reference statements)
0
12
0
1
Order By: Relevance
“…IGF-BP3 is the most abundant binding protein, accounting for over 80% of IGF-1 binding (30). Interestingly, levels of both IGF-1 and IGF-BP3 have been shown to be reduced in critical illness (53). Prior studies demonstrate a decrease in the incidence of sepsis by pretreatment with IGF-1 in a murine model of thermal injury (17) and improved survival in sepsis by pretreatment with IGF-1 (18).…”
mentioning
confidence: 99%
“…IGF-BP3 is the most abundant binding protein, accounting for over 80% of IGF-1 binding (30). Interestingly, levels of both IGF-1 and IGF-BP3 have been shown to be reduced in critical illness (53). Prior studies demonstrate a decrease in the incidence of sepsis by pretreatment with IGF-1 in a murine model of thermal injury (17) and improved survival in sepsis by pretreatment with IGF-1 (18).…”
mentioning
confidence: 99%
“…Another study, by Onenli-Mungan et al showed the same GH/IGF-I pattern in pediatric septic children but they observed that hypoglycemia could be a contributing factor to elevated GH levels 15 . Gardelis et al also did a prospective study with septic and trauma children and found the same GH/IGF-I response in trauma and septic patients 12 . Huysman et al described a suppressive effect of 2 days of dexametasone treatment on serum GH levels, without an acute decline in serum IGF-I levels in 10 very preterm artificially ventilated infants with bronchopulmonary dysplasia 16 .…”
Section: Introductionmentioning
confidence: 85%
“…Demling et al suggests that rhGH should not be given to critically ill adult patients, with the exception of burn and trauma 11 . Among the hormonal changes, the modulation in the GH/ IGF-I axis in pediatric population with hypercatabolic state is not entirely clear 12 . Balcells et al found a GH-resistant state in postoperative children following cardiac surgery characterized by an elevation of GH secretion that was not followed by IGF-I and IGFBP-3 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of anabolic hormones to enhance anabolic activity in critically ill patients would seem logical, but no consistent benefits have been shown in clinical studies. In acutely critically ill patients, growth hormone secretion is generally increased but there appears to be peripheral growth hormone resistance, with reduced levels of its main effector molecule, insulin-like growth factor-1, as well as insulin-like growth factor-binding and growth hormone-binding proteins (45,46). In more prolonged critical illness, growth hormone levels are decreased, and growth hormone resistance is no longer present.…”
Section: Endocrine Supportmentioning
confidence: 99%